Tailoring the Band Gap in Codoped GaN Nanosheet From First Principle Calculations - Ke, Changjiao; Tian, Chunling; Gan, Yundan (Frontiers in Materials, 2020)
To develop an efficient photocatalyst with intense visible light absorption and high charge mobility is important but still remains a problem. In this work, we have explored the electronic properties of C-monodoped, C-Ge and C-Sn codoped GaN nanosheets by the hybrid density functional theory, in order to find the excellent photocatalytic materials. Results indicate the monodoping of C introduces the unoccupied impurity states inside the band gap that serve on recombination centers. Thus the C monodoping is not suitable to ameliorate visible light absorption. Moreover, the C-Ge and C-Sn codoping not only reduce successfully band gap of nanosheet GaN, but also avoid the unoccupied impurity states. The charge-compensated C-Ge and C-Sn codoped GaN nanosheets are energetically favorable for hydrogen evolution but not insufficient to produce oxygen, indicating that they could serve as Z-scheme photocatalysts. In particular, the minimum defect formation energy of C-Ge is negative and lowest. The C-Ge codoped GaN system has dynamic stability. So, the C-Ge codoped nanosheet GaN is one of the most prospective candidates for decompose hydrogen from water.